Deforestation in Brazilian Amazonia and Global Warming - Fearnside, Philip M (Annals of Arid Zone, 2016)
Deforestation in Brazilian Amazonia makes a substantial contribution to global emissions of greenhouse gases because of the high rates of forest clearing and the high biomass per hectare of forest. Half of the dry weight of the trees is carbon, and this is released primarily as C02 or CH4 when the felled trees are burned or when any unburned wood decays. Amazonia is not only important to global emissions because of the emissions today, but also because the region has a vast area of forest that remains uncleared. While some tropical forest regions of the world also have rapid clearing and high emissions today, this will not last long because the forest in these areas is coming to an end. The large unreleased carbon stock in Amazonia means that any policy changes that affect deforestation will have an important effect on future emissions. Uncertainty is still high regarding the magnitude of net emissions from Amazonia, including estimates of biomass and carbon stock, burning efficiency (and related trace-gas emissions), and the biomass and carbon dynamics of the landscape that replaces the forest. Substantial progress has been made in reducing the uncertainty surrounding these key components, but the additional information also serves to reveal the scale of our ignorance. Despite these uncertainties, it is clear that deforestation emissions are large and that the environmental gain from reduced deforestation and degradation (REDD) is therefore also large. Key words: Carbon, environmental services, ecosystem services, greenhouse effect, rainforest, tropical forest.